Changes in Denitrification Potentials and Riverbank Soil Bacterial Structures along Shibetsu River, Japan. (26th June 2018) - Uchida, Yoshitaka; Mogi, Hirosato; Hamamoto, Toru; Nagane, Miwako; Toda, Misato; Shimotsuma, Moe; Yoshii, Yui; Maeda, Yuto; Oka, Miyuki
Abstract : Riverbank soil ecosystems are important zones in terms of transforming inorganic nitrogen (N), particularly nitrate (NO3 − -N), in soils to nitrous oxide (N2 O) gases. Thus, the gasification of N in the riverbank soil ecosystems may produce a greenhouse gas, N2 O, when the condition is favourable for N2 O-producing microbes. One of the major N2 O-producing pathways is denitrification. Thus, we investigated the denitrification potentials along Shibetsu River, Hokkaido, Japan. We sampled riverbank soils from eight sites along the Shibetsu River. Their denitrification potentials with added glucose-carbon (C) and NO3 − -N varied from 4.73 to 181  μ g·N·kg −1 ·h −1 . The increase of the denitrification after the addition of C and N was negatively controlled by soil pH and positively controlled by soil NH4 + -N levels. Then, we investigated the changes in 16S rRNA bacterial community structures before and after an anaerobic incubation with added C and N. We investigated the changes in bacterial community structures, aiming to identify specific microbial species related to high denitrification potentials. The genus Gammaproteobacteria Aeromonadaceae Tolumonas was markedly increased, from 0.0 ± 0.0% to 16 ± 17%, before and after the anaerobic incubation with the excess substrates, when averaged across all the sites. Although we could not find a significant interaction between the denitrification potential and the increase rate of G. Aeromonadaceae Tolumonas, our study suggested that along the Shibetsu River, bacterial response to added excess substrates was similar at the genus level. Further studies are needed to investigate whether this is a universal phenomenon even in other rivers.